Hypomethylation of NLRP3 gene promoter discriminates glucocorticoid‐resistant from glucocorticoid‐sensitive idiopathic nephrotic syndrome patients. Issue 3 (25th January 2021) - Lucafò, Marianna; Granata, Simona; Bonten, Erik J.; McCorkle, Robert; Stocco, Gabriele; Caletti, Chiara; Selvestrel, Davide; Cozzarolo, Alessio; Zou, Chan; Cuzzoni, Eva; Pasini, Andrea; Montini, Giovanni; et al.
Abstract : Abstract: To assess whether NLRP3 gene promoter methylation was able to discriminate glucocorticoid (GC)‐resistant from GC‐sensitive idiopathic nephrotic syndrome (INS), patients with minimal change disease (MCD) or focal segmental glomerulosclerosis (FSGS), we measured the methylation level of NLRP3 promoter in DNA from peripheral blood cells of 10 adult patients with GC‐resistant FSGS already in hemodialysis and 18 patients with GC‐sensitive INS (13 MCD/5 FSGS) and in 21 pediatric patients with INS with MCD/FSGS before starting any treatment. Association of NLRP3 inflammasome with GC resistance was recapitulated in vitro in monocytic cell lines (THP‐1 and U937). In both adults and pediatric patients, NLRP3 promoter methylation was significantly reduced in GC‐resistant compared with GC‐sensitive patients. Indeed, NLRP3 methylation distinguished GC‐resistant and GC‐sensitive patients (area under the receiver operating characteristic curve [AUROC] 86.7% in adults, p  = 0.00019, and 73.5% in children, p  = 0.00097). NLRP3 knock‐down augmented sensitivity to GCs in THP‐1 cells, whereas NLRP3 inflammasome activation lowered GC receptor concentration, increasing GC resistance in U937 cells. Our results uncovered a new biological mechanism by which patients with INS may acquire GC resistance, that could be used in future as a novel noninvasive diagnostic tool. Study Highlights WHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? ☑ Approximately 80% of patients with idiopathic nephrotic syndrome (INS) respond to glucocorticoids, with the remaining 20% being steroid‐resistant. WHAT QUESTION DID THIS STUDY ADDRESS? ☑ Whether NLRP3 gene promoter methylation was able to discriminate glucocorticoid‐resistant from glucocorticoid (GC)‐sensitive INS. WHAT DOES THIS STUDY ADD TO OUR KNOWLEDGE? ☑ In both adults and children, NLRP3 promoter methylation was significantly reduced in leukocytes of patients with GC‐resistant compared with GC‐sensitive INS. NLRP3 inflammasome activation lowered GC receptor concentration and augmented GC resistance, whereas NLRP3 knockdown increased sensitivity to GCs in cell lines representative of monocytes (U937 and THP1). HOW MIGHT THIS CHANGE CLINICAL PHARMACOLOGY OR TRANSLATIONAL SCIENCE? ☑ Our findings uncovered a new biological mechanism whereby patients with INS may develop resistance to GCs that could be used in the future as a novel noninvasive diagnostic tool.